(untitled) (Ágora de Heterodoxias, 2024)
This article started from hermeneutic analysis through an overview of different theorists who address the topic and was supported by an interpretative discourse based on discussions by Habermas and Gadamer, who expose that all methods produce hermeneutic fruits as a different perspective of methodological application. the intention of translating epistemology and hermeneutics to the theoretical framework and overcoming the classification to which they are constantly subjected as methodologies and methods. To this end, an epistemological reflection was also carried out by theorizing the highlighted aspect of the research “managerial success” through semantic analysis as a scientific act in the generation of new knowledge. It was concluded that the interpretation of managerial success is accompanied by different factors of disciplinary action that are subject to the situational reality of the organization and the execution of strategic actions that arise from the decision-making processes.